USE OF 0.01% METHYLENE BLUE AS A SIMULATOR OF LOCAL ANESTHETIC DISPERSION IN THE THORACIC AND PELVIC LIMBS OF DOGS AND CATS (Editora Impacto Científico, 2025)
Local anesthesia is a widely used technique in veterinary medicine for the management of acute and chronic pain, as well as during the trans- and postoperative periods in dogs and cats. Among its modalities, infiltration anesthesia stands out, which consists of administering the drug into tissues that are not necessarily close to specific nervous structures. Methylene blue has been employed as a standardization method to evaluate the dispersion of anesthetic solutions in different techniques and animal positioning. This study aimed to experimentally analyze the dispersion of a 0.01% methylene blue solution in the thoracic and pelvic limbs of dogs and cats. Three cadavers — two dogs and one cat — were used, divided into two groups: refrigerated and thawed cadavers (RD) and recently deceased cadavers (OS). The local anesthesia technique was applied in different tissue planes of the animals. The results showed good dispersion of the dye in the applied areas, with staining observed in the median and common fibular nerves of the thoracic and pelvic limbs, respectively, as well as significant penetration into the surrounding musculature. In one of the cadavers from the RD group, the dye even reached the periosteum. The findings indicate that local infiltration anesthesia can promote blockade of relevant nerve structures and widely reach the musculature of the targeted regions. This reinforces its potential in composing multimodal analgesia strategies in small animal clinical practice.DOI: https://doi.org/10.56238/edimpacto2025.090-070